(untitled) (Revista Apotheke, 2025)
This article reports on methodological experiments in the methodological experiments in the Pedagogical Studio Course for second-year high school teacher training classes, with an emphasis on creating artist journals as Logbooks. Originating from a dialogue among three Art teachers, the initiative aimed to enrich the artistic, aesthetic, poetic, and sensitive training of future teachers. This is a new course that began in 2022, with a syllabus that allows for the creativity of the teacher to implement it, and this has been the focus of development. To achieve this, we used (self)biographical and narrative approaches, along with a diverse theoretical framework in constructing this text. These methodologies not only enrich artistic training but also promote aesthetic and poetic sensitivity through Logbooks, which go beyond merely recording objective events to capturing observed subjectivities, fostering a comprehensive visual creation experience.